Structure and installation of modern science: critical contributions to the theoretical-methodological debate - Bastos, Júlia Érika Moreira (2021)
From the mid-16th century the scientific model of doing research achieves the shapes that would influence contemporaneous research all over the world. To undersdand it is a fundamental piece to understand nowadays science. Based on the marxian method of investigation, which seeks the essency of the real, the contradictory and in constant movement provoked by the mankind, the objective of this work is to present the relation in the transition process between feudalism and capitalism and the establishment of the science model that goes along with the system. Thus, we verify the passage between the old and the new model for producing knowledge, in which the criteria of truth and the notion of reality itself pass through historical modifications, associated to their respective dominant classes. There is the transformation from a comprehension of nature by the contemplation, particular to medieval era, to the practice of modern qualitative and quantitative measurement. Therefore, the experimental proof takes the central role and with it the required methodology and instrumental. We conclude that the contributions of Copernicus, Galileu e Newton are inside of a process of consolidation of the capitalist system, as a science doing associated to the new socially imposed productive interests, whose greatest benefits would be harvested specially by the rising burgeois class.